Indigenous knowledge of veterinary medicinal plant use in cattle treatment in southwestern Burkina Faso (West Africa) - Traoré, L.; Yaro, V.S.O.; Soudré, A.; Ouédraogo-Koné, S.; Ouédraogo, D.; Yougbaré, B.; Zoma, B.L.; Hien, M.; Guissou, M.L.; Traoré, A.; Mészáros, Gábor; Wurzinger, Maria; et al. (Elsevier, 2020)
Traditional livestock husbandry is of great socio-economic importance for farmers and pastoral populations in Burkina Faso in general and in particular, those in the Southwestern region. The aim of our study is to inventory medicinal plants in cattle husbandry in the Poni province. Methodology consisted of semi-structured interviews; individual conversations with local specialists in the use of local plants. A total of 120 informants were interviewed (60 specialists, 60 non-specialist farmers) across three sites (Bouroum–Bouroum, Loropéni and Kampti) where a community based cattle breeding program has taken place. The results showed that 26 medicinal plants for veterinary use, distributed across 23 genera and 15 families were well known. In total, 9 important cattle diseases for which medicinal plants are used have been recorded. The most frequent diseases reported were foot and mouth disease (22%) and animal trypanosomosis (21%). Among the six (06) modes of preparation recorded for disease treatment, decoction was the most used (62%). Statistical analyses revealed a significant difference between men and women (p = 0.002) with medicinal plant knowledge. Men know more medicinal plants than women do. The results have indicated a disparity of medicinal plant knowledge according to age classes. The results also revealed a significant difference (p = 0.028) of plants recognised by seven ethnic groups. Knowledge of different medicinal plants for veterinary use among the ethnic groups was influenced by the family income source and the main activity. The informant consensus factor (0.5) showed that all the informants agreed on the importance of medicinal plant conservation. Promoting the veterinary use of the plants recorded in this study could be a key to their conservation.